PENGARUH PEMBERIAN JUS NANAS TERHADAP PROSES PENYEMBUHAN LUKA PERINEUM PADA IBU NIFAS - Dewi, Ratna; Dielsa, Maya Fernanda (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
Based on the targets (Millennium Development Goals), one of the 2020 SDGs targets, namely MMR 230 per 100,000 live births and IMR 24 per 1,000 live births shows that MMR and IMR in Indonesia in 2020 MDGs are then followed by the SDGs (Sustainable Development Goals), one one of the SDGs targets is to reduce MMR to less than 102 per 100,000 live births and IMR 12 per 1,000 live births by 2030. The purpose of this study was to find out whether there was an effect of giving pineapple juice on the healing process of perineal wounds in postpartum. This study used a pre-experimental research design with the-static-group comparison which was carried out at PMB Martini, S.ST from January to March 2023. The population was all first degree and second degree post partum mothers at PMB Martini, S.ST Padang Pariaman and a sample of 20 people with purposive sampling technique.From the results of the study that were not given pineapple juice, the respondents experienced perineal injuries with a value of 70%. While healing the perineal wound given pineapple juice with a value of 80%. There is an effect of pineapple juice on the healing process of perineal wounds in postpartum women where the value is significant p = 0.028 (<0.005).In conclusion, there is an effect of pineapple juice on the healing process of perineal wounds in postpartum women. Expected to help mothers through the postpartum period, especially for mothers who experience injuries to the perineum. giving pineapple juice can be an alternative to accelerate wound healing in the perineum.Keywords: Giving Pineapple Juice, Perineal Wounds, Postpartum Mothers.